2014
DOI: 10.1007/s10529-014-1647-6
|View full text |Cite
|
Sign up to set email alerts
|

Two natural glucomannan polymers, from Konjac and Bletilla, as bioactive materials for pharmaceutical applications

Abstract: Next-generation biomaterials are expected to possess both desirable mechanical features and unique biological functions. Recently, two plant-derived glucomannans (GMs)-Konjac glucomannan (KGM) and the polysaccharide of Bletilla striata (BSP)-have emerged as new sources for development of biomaterials. They have been fabricated into drug delivery vehicles and wound healing dressings in varying shapes and sizes, and demonstrated strong gelling properties, high biocompatibility and remarkable convenience for proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…B. striata polysaccharide (BSP) is extracted from B. striata and consists of α-mannose, β-mannose and β-glucose (17). BSP has a number of biological functions, including anti-inflammatory (18), anti-tumor (19), anti-fibrosis (20) and antibacterial (21) properties, as well as inducing endothelial cell proliferation and vascular endothelial growth-factor expression (16).…”
Section: Introductionmentioning
confidence: 99%
“…B. striata polysaccharide (BSP) is extracted from B. striata and consists of α-mannose, β-mannose and β-glucose (17). BSP has a number of biological functions, including anti-inflammatory (18), anti-tumor (19), anti-fibrosis (20) and antibacterial (21) properties, as well as inducing endothelial cell proliferation and vascular endothelial growth-factor expression (16).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other groups, the special surface structures of BSMPs (350–250  μ m) enable them to promote blood/particle aggregation and to form rapid sealants on wound surfaces to achieve rapid hemostasis. Recent studies have shown that B. striata contains numerous polysaccharides that have been identified as major active components responsible for the various biological effects [12]. Furthermore, bioactivity evaluations have revealed hemostatic activities of B. striata polysaccharides [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is especially used in Japanese food industries as low calorie food supplement. Konjac gum films can be used for controlled release of medicines [31].…”
Section: Polysaccharides and Healthmentioning
confidence: 99%